Association of the time in targeted blood glucose range of 140 to 180 mg/dL with the mortality of critically ill patients with diabetes: analysis of the MIMIC-IV database - Huimin Ye; Zilan Ma; Qunchuan Zong; Qiang Zhu; Yufei Yan; Shengmei Yang; Pengyue Xiang; Huajie Zou (Journal of Clinical & Translational Endocrinology, 2025)
Background: Time in range (TIR), a glycemic control metric, is increasingly linked to diabetes outcomes. A target of 140–180 mg/dL is recommended for critically ill hyperglycemic patients. Methods: This cohort study analyzed 6,047 critically ill diabetic patients (median age 68, 62.3 % male) from the MIMIC-IV database. TIR (140–180 mg/dL) was defined as the percentage of time within the target glucose range over 24 h. Patients were stratified by TIR quartiles. Outcomes included all-cause mortality, ICU mortality, in-hospital mortality, and 28-day mortality. Cox models assessed TIR-outcomes relationships. Results: Higher TIR correlated with lower mortality. Adjusted HRs for all-cause mortality were 1.00 (Q1), 0.63 (Q2), 0.56 (Q3), and 0.65 (Q4) (p for trend < 0.001). Similar trends were observed for in-hospital mortality (Q4 vs. Q1: HR 0.79, 95% CI: 0.64–0.97). Each 10 % TIR increase reduced all-cause mortality by 8 % (HR 0.92, 95 % CI: 0.88–0.95). Nonlinear dose–response relationships were significant (p < 0.001), with stronger effects in patients < 60, males, and those with myocardial infarction or cancer history (p for interaction < 0.05). Conclusions: Higher TIR (140–180 mg/dL) is associated with reduced mortality in critically ill diabetic patients, suggesting that TIR is a valuable metric for glycemic management in the ICU.